Synthesis of anthraquinone analogues and their antiplasmodial activity / Nor Hadiani Ismail, Rohaya Ahmad and Che Puteh Osman - Ismail, Nor Hadiani; Ahmad, Rohaya; Osman, Che Puteh (Research Management Institute (RMI), 2011)
Several anthraquinones such as 2-formyl-3-hydroxyanthraquinone, damncanthal and emodin were known antiplasmodial agents. Anthraquinones like other aromatic substances may undergo bioreduction and produce oxygen radicals thereby rendering the malarial parasite more susceptible to oxidative stress leading to the death of parasites. Anthraquinones isolated from the roots of Rennellia elliptica demonstrated interesting antiplasmodial activity. The activity however, varies depending on substitution pattern of the anthraquinone skeleton. Thus, the synthesis of 9,10-anthraquinones mimicking natural anthraquinones from R. elliptica was warranted and their antiplasmodial activity was evaluated to examine the possible structure-activity relationship of 9,10-anthraquinones and their antiplasmodial activity. The analogues of bioactive anthraquinones were synthesized through Friedel-Craft reaction between phthalic anhydride and various benzene derivatives in the presence of eutectic mixture of aluminium chloride and sodium chloride. The antiplasmodial activity was determined based on inhibition of the compounds against Plasmodium falciparum (3D7) growth in vitro. Thirty two compounds were successfully synthesized throughout the study. The strongest inhibition against malarial parasite was shown by 1,3-dihydroxy-6-methyl-9,10-anthraquinone with IC50 value of 0.02 μM. In general, the arrangement of substituents in symmetrical manner is essential for effective antiplasmodial activity. For dihydroxylanthraquinones, the activity is favourable when the substituents are meta-arranged and symmetrical to methyl group at C-6. For dimethoxyanthraquinones, the activity is more potent when the substituents are orthoarranged at C-1 and C-2 and symmeticaly to methyl substituent at C-6. This observation correlates well with anthraquinones substituted with hydroxyl and methyl substituents. Quantitative structure-activity relationship to further examine the potential of anthraquinones as antiplasmodial agent should be pursued.